Design and Test of Dual Actuator Nose Wheel Steering System for Large Civil Aircraft - Ming Zhang; Rongmin Jiang; Hong Nie (International Journal of Aerospace Engineering)
In order to improve aircraft ground handling characteristics and airport working efficiency, large handling angle and torque are requested for the nose wheel steering system of large civil aircraft. A following swivel selector valve is firstly designed to meet the demand for the hydraulic pressure commutating as soon as the dual actuator nose wheel steering mechanism passes through its dead center position. Considering the multiple objective functions of nose wheel steering mechanisms, those core design parameters are multiobjective optimized. A nose wheel steering electrohydraulic servo system with handling and antishimmy functions is designed for the steering mechanism. Then the prototypes of the steering mechanism and electrohydraulic servo system are researched to validate the design. Using the swing actuator to provide the load torque and ground excitation, the steering test bench is prepared to test the system working. The steering test and the antishimmy test are conducted to verify the functions of the system. The test results, such as steer angle, steer torque hydraulic pressure, and antishimmy torque, are analyzed in detail and compared with the theoretical results. The results show that the property of the prototype achieves the design objectives, such as work mode, steer angle, and steer torque.